Notes for the general paediatrician: managing thyrotoxicosis in children and young people - Indraneel Banerjee; Leena Patel; Marianna Vidouris; Beverly Hird; Lesley Tetlow; Christopher Worth; Anjali Date; Anas Jasser (BMJ Publishing Group, 2022)
Thyrotoxicosis due to hyperthyroidism is a serious disorder in childhood often presenting to general paediatricians with a range of clinical manifestations. The commonest cause is Graves' disease, an autoimmune disorder resulting from thyrotropin receptor stimulation by autoantibodies. Early recognition and accurate interpretation of investigations are essential to achieve and maintain a euthyroid state. This will not only optimise growth, development and transition from childhood to young adult life but also avoid the potentially severe and life-threatening complications of acute thyrotoxicosis. In this review, we have focussed on the general paediatrician's perspective of the presentation and management of thyrotoxicosis and the need to network with specialist paediatric endocrine centres to optimise patient care. We have discussed nuances of therapy, side effects and long-term outcomes, while recognising that limited remission rates in this age group often necessitate more definitive management. While carbimazole is usually used as first-line medical therapy, we have provided useful information to guide paediatricians in the discussion of individualised safe and effective treatment plans for both short-term and long-term management.